Study on the mortality in Ecuador related to dietary factor - Juan Alejandro Neira-Mosquera (Nutrición Hospitalaria, 2013)
Diet is an important factor related to the development of numerous diseases. In developing countries like Ecuador, this aspect is not considered as priority however, the study of the incidence of certain diet-related diseases could help to assess consumption habits of a country from a Public Health perspective and support national nutrition policies and programs. The objective the present study is to investigate the mortality rate of certain diet-related diseases in Ecuador and its possible relationship with Ecuadorian consumption habits. For that, mortality rates (2001-2008) associated with five different disease groups related to dietary factors (cancer of colon, cerebrovascular diseases, cardiovascular diseases, diabetes mellitus and liver diseases) were collected, analyzed and compared to consumption patterns in Ecuador. According to results, Ecuador has a low level of cancer of colon in comparison with developed countries (e.g. Spain). The group with the highest number of deaths corre- sponded to cardiovascular diseases followed by cerebrovas- cular diseases. The mortality study per province revealed that Amazonian provinces showed few deaths in relation to other provinces in Ecuador. This could be due to different factors including fails in the disease surveillance informa- tion systems, environmental factors and consumption patterns. In this sense, further investigation on native prod- ucts consumption such as “chontaduro” might help to find valuable foods contributing to healthier Ecuadorian diet. These results, though preliminary, evidence that a major effort should be made by national and international organi- sations to collect data on consumption patterns and nutri- tional aspects of the Ecuadorian population in order to better support the development of effective food security and nutrition policies.